Application Effect of Case Management Mode Combined with ERAS in Elderly Patients with Hip Fracture. (30th September 2021) - Peng, Na; Li, Jing
Abstract : Objective . To explore the effect of the case management mode combined with enhanced recovery after surgery (ERAS) in elderly patients with hip fracture. Methods . A total of 102 elderly hip fracture patients admitted to our hospital from June 2018 to December 2019 were selected. The patients with hip fracture were divided into the control group ( n = 51) and the observation group ( n = 51) by the random number table method. The control group adopts the conventional nursing mode, and the observation group adopts the case management mode combined with ERAS. The bed activity time, hospitalization time, total hospitalization expenses, and the satisfaction of patients were observed. The numeric rating scale (NRS) was used to assess the patient's pain before treatment and at 1, 3, and 5 days after treatment. The Harris score was used to assess the patient's joint motor function before treatment and at the 8th week after treatment. The perioperative complications of the two groups were compared. Result . After treatment, the observation group was better than the control group in terms of out of bed activity time, hospitalization time, total hospitalization expenses, and the satisfaction of patients (P < 0.05 ). Before treatment, there was no significant difference in NRS scores between the two groups (P > 0.05 ). After treatment, the NRS scores of the two groups were lower than before treatment, and on days 1, 3, and 5 after treatment, the NRS scores of the observation group were lower than those of the control group (P < 0.05 ). Before treatment, there was no difference in the Harris score between the two groups (P > 0.05 ). At the 8th week after treatment, the Harris scores of the two groups were higher than those before treatment, and the Harris scores of the observation group were higher than those of the control group (P < 0.05 ). The total incidence of perioperative complications in the observation group (4/51) was lower than that in the control group (13/51) (P < 0.05 ). Conclusion . The application of the case management mode combined with ERAS nursing in elderly patients with hip fracture can improve the clinical symptoms of patients, improve the therapeutic effect, and reduce the occurrence of complications, which is worthy of clinical application.